Touch in late medieval English theatre - Witherden, S (2019)
This thesis examines touch in late medieval English theatre, considering tactile encounters on stage and the role of touch in audience experience. Although touch is increasingly attracting attention in medieval studies, theatre has thus far been an exception to this trend. To rectify this, I focus primarily—though not exclusively—on biblical drama, especially the York and N-Town Plays. My methodology is threefold, synthesizing lexical analysis, interdisciplinary comparisons of drama and art, and materially informed readings of medieval theatre.